Why Do We Need New Gene Therapy Viral Vectors? Characteristics, Limitations and Future Perspectives of Viral Vector Transduction - Tomanin, R.; Scarpa, M. (Current Gene Therapy, 2004)
The use of viruses to transduce genes of interest into mammalian cells has been extremely revolutionary, both in terms of laboratory research and for clinical purposes. This approach has allowed expression and over-expression of proteins of interest as well as the understanding of both virus life cycles and eukaryotic cell mechanisms. Beginning in the late eighties gene transduction has been applied to clinical trials but mainly restricted to cancer treatment and genetic diseases. More recently it has been proposed for the cure of infectious diseases (AIDS), vascular diseases and others (Alzheimer's and Parkinson's disease). Viral vectors have been progressively modified in order to increase their transduction efficiency and to reduce their toxicity, immunogenicity and inflammatory potential. In this respect, much has been done in the last few years. By adding genes belonging to other viral species to the vectors' DNA, scientists were able to re-direct their tissue-specificity or to control protein expression. More recently, in the attempt of overcoming the limitations of each viral species, so-called chimeric viral vectors have been generated by combining favourable features of two or more different viruses into one. This review summarises the main characteristics of the most common viral vectors, including their advantages, limitations and possible future applications. It also briefly discusses development and evolution of chimeric vectors, treated in more details along this entire issue. Finally, we evaluate basic safety aspects, mandatory to consider for the clinical application of viral gene transduction.
Keywords: viral vectors